Synaptic input as a directional cue for migrating interneuron precursors - Wefers, Annika K.; Haberlandt, Christian; Tekin, Nuriye B. (Development, 2017)
Skip to Next Section - During CNS development, interneuron precursors have to migrate extensively before they integrate in specific microcircuits. Known regulators of neuronal motility include classical neurotransmitters, yet the mechanisms that assure interneuron dispersal and interneuron/projection neuron matching during histogenesis remain largely elusive. We combined time-lapse video microscopy and electrophysiological analysis of the nascent cerebellum of transgenic Pax2-EGFP mice to address this issue. We found that cerebellar interneuronal precursors regularly show spontaneous postsynaptic currents, indicative of synaptic innervation, well before settling in the molecular layer. In keeping with the sensitivity of these cells to neurotransmitters, ablation of synaptic communication by blocking vesicular release in acute slices of developing cerebella slows migration. Significantly, abrogation of exocytosis primarily impedes the directional persistence of migratory interneuronal precursors. These results establish an unprecedented function of the early synaptic innervation of migrating neuronal precursors and demonstrate a role for synapses in the regulation of migration and pathfinding.
Gesehen am 04.04.2019